Evaluation of spectral radiative properties of gases in high-pressure combustion. (April 2022) - Westlye, Fredrik R.; Hartz, Benjamin A.K.; Ivarsson, Anders; Fateev, Alexander; Clausen, Sønnik
Highlights: High pressure and temperature spectroscopic data of CO2 Pseudo-Lorentzian line profile for CO2-N2 at elevated pressure and temperature validated against spectroscopic data. Pseudo-Lorentzian line profile correlated with high pressure and temperature data for CO2-N2 mixtures. Pseudo-Lorentzian line profile for H2O at elevated pressure validated against spectroscopic data from literature. Abstract: Radiative heat transfer affects local flame temperatures, and thus pollutant formation in high-pressure diffusion flames but the radiation properties of major gas species at pressures and temperatures relevant for combustion engines are not well known. In order to facilitate radiative transfer calculations in these types of flames, new and already published CO2 and H2 O absorption spectra at high pressure and temperatures have been used to validate their modelled spectra based on the HITEMP 2010 database. Corrections for non-Lorentzian behavior of collisional-broadened lines have been evaluated, where an adjustable pseudo-Lorentzian line profile has been correlated for CO2  − N2 mixtures over a wide range of pressure, temperature and concentration. A fixed pseudo-Lorentzian line profile was found to give similar performance to previous empirical line corrections when comparing to available experimental H2 O data over a relatively wide pressure and temperature range. The work has led to the release of an in-house MATLAB code, named RadISpeC freely available for download. The code efficiently produces spectra for radiation calculations for both soot and gas at high pressures and temperature.